Cover Pages - UP Institute of Creative Writing, Likhaan (Likhaan: The Journal of Contemporary Philippine Literature; Vol 14 No 3 (2020): Dx Machina: Literature in the Time of COVID-19 Issue #2, 2021)
Cover Pages